Пам’яткоохоронна діяльність Київського товариства охорони пам’яток старовини й мистецтва впродовж 1910–1913 рр.: становлення та розвиток - Качковська, Леся; Kachkovska, Lesya (My University, 2016)
У статті висвітлено становлення й розвиток діяльності Київського товариства охорони пам’яток старовини та мистецтва (далі – КТОПСІМ). Досліджено процес реалізації ним організаційних і статутних питань. Проаналізовано пам’яткоохоронний аспект роботи КТОПСІМ на Правобережній Україні за матеріалами звітної документації 1910–1913 рр.The thesis describes details with the analysis of the artifacts studies and artifacts protection activities carried out by the Kyiv Society for the Protection of the Artifacts of Antiquities and Arts (KSPAAA). A special attention has been paid to the investigation of the legislative basis of the society work, its structure and personnel. The theoretical principles of the KSPAAA's work, its main directions and forms were found out. The kinds and types of the regional artifacts that were studied by the society were pointed out too.
Activity of Kyiv Association for Protection of Monuments to the Past and Monuments of Art Based on Materials of Ancient Monuments and Art During the 1910-1913 Biennium: Formation and Development
Keywords: Київське товариство охорони пам’яток старовини і мистецтва; культурна спадщина; пам’яткознавча діяльність; пам’яткоохоронна робота; cultural monuments; measures connected with the study and protection of cultural monuments; Kyivschchina; Uman